Si fault de fain perir les innocens… - Maria Helena Marques Antunes (Carnets)
The poems discussed in this study form two poetic cycles devoted to moral edification. The first set, a ballade by Eustache Deschamps and an anonymous rondeau, brings together two poetic forms with different aesthetic assumptions. The second is a series of six ballads situated at the end of the long lyrical suite of Jardin de plaisance et fleur de rhétorique. The dialogical relationship established and cultivated by the anthology's editor between the Deschamps ballade and the anonymous rondeau as well as between the ballades of the second group reveals that the selection of the poems and their placement in the collection is part of an editorial programme aimed at promoting ethical reflection in the reader, which deserves to be emphasised, as the vast majority of the texts collected are in the courtly register.